Air‐Pressure‐Assisted Pen‐Nib Printing for 3D Printed Electronics. Issue 6 (5th November 2021) - Ahn, Jinhyuck; Sim, Ho Hyung; Kim, Je Hyeong; Wajahat, Muhammad; Kim, Jung Hyun; Bae, Jongcheon; Kim, Seonghyeon; Pyo, Jaeyeon; Jeon, Chang Jun; Kim, Bum Seok; Baek, Sung Hyun; Seol, Seung Kwon
Abstract: 3D printed electronics employing direct‐ink‐writing methods are promising alternative manufacturing technologies for realizing structural electronics. The emerging demand for accessible, cost‐effective, and rapid writing calls for novel approaches to print functional components onto nonflat and 3D architectures. This study presents a novel air‐pressure‐assisted pen‐nib printing approach producing electrical and functional components with various material inks on flat and 3D surfaces. Based on the inks' rheological properties, the ejected ink's quantity through the nib is manipulated via air pressure; thus, the printed line width is controlled. This strategy also achieves the viscosity range extension of printable inks by enabling printing inks that cannot be used in general pen‐based printing. Three functional inks with different rheological properties—Ag catalyst ink for Cu electroless deposition, Ag‐PEDOT:PSS ink, and thermochromic pigment inks are designed. Several electrical and functional components, such as highly conductive Cu interconnects, Cu spiral coils for wireless power transfer receivers, flexible heaters, and matrix data codes based on temperature‐responsive color transitions are demonstrated. Furthermore, parallel printing with a multi‐nib print‐head is demonstrated for improving the printing speed and manufacturing scalability. The authors believe that this novel approach is promising as a manufacturing technique for realizing 3D printed electronics. Abstract : Air‐pressure‐assisted pen‐nib printing that can control ink ejection by negative ( P n ) and positive ( P p ) air pressure is developed. Several functional patterns and electrical components are printed using three inks with different rheological properties, such as Ag catalyst ink for Cu electroless deposition, Ag‐decorated PEDOT:PSS ink, and thermochromic pigment inks. Parallel printing with multi‐nib print‐head is also demonstrated.